Solving the University course timetabling problem using bat inspired algorithm - Limota, Ushindi; Mujuni, Egbert; Mushi, Allen R. (Tanzania Journal of Science, 2024)
Article published by the Tanzania Journal of Science Vol. 47 No. 2 (2021)